(untitled) (Homoeopathy for All, 2023)
Aristotle, the famous ancient Greek philosopher, has rightly said, “Educating the mind without educating the heart is no education at all.” This means, the teachers should teach their students not mechanically, nor merely as a part of their duties because they are paid for this, but they should be heartily involved while teaching their students. It is an undeniable fact that the students pay more respect to their teachers, than anyone else. So, the love and affection with which the teachers teach in the classrooms have lasting effects in the minds of their disciples, even outside the boundaries of their classrooms. Our society keeps the teachers in high esteem, pays immense respect to them because they know that the latter have a vital role in not only building up the future careers of their siblings, but also their character, morale, behaviour, domestic and social relationships, and above all, for transforming them to good human beings blended with humane attitude and compassion.